2016
DOI: 10.1111/ggi.12806
|View full text |Cite
|
Sign up to set email alerts
|

Screening for postoperative delirium in patients with acute hip fracture: Assessment of predictive factors

Abstract: The present results show that CAM-ICU is highly sensitive and specific to identify delirium in hip fracture patients in the postoperative period. Among all of the risk factors, cognitive impairment and depressive mood were strongly associated with postoperative delirium. We suggest that a preoperative assessment of cognition and depression might be useful for identifying patients with a higher risk of postoperative delirium. Geriatr Gerontol Int 2017; 17: 919-924.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…Available data suggest that preexisting cognitive impairment predicts incident POD, which, in turn, can impair long‐term cognitive functioning . Preoperative cognitive impairment has also been linked to the incidence of other adverse outcomes, including postoperative complications, longer hospital stay, and functional decline .…”
Section: Discussionmentioning
confidence: 99%
“…Available data suggest that preexisting cognitive impairment predicts incident POD, which, in turn, can impair long‐term cognitive functioning . Preoperative cognitive impairment has also been linked to the incidence of other adverse outcomes, including postoperative complications, longer hospital stay, and functional decline .…”
Section: Discussionmentioning
confidence: 99%
“…Those studies showed a contrasting sensitivity from 25-80% and a high specificity (97-99%). 18,19 The data from previous research at the current study site showed that approximately 50% of patients aged ≥60 years were admitted postoperatively to the ICU. 20 From a hospital perspective, the uniform utilization of a single delirium screening tool for all postoperative older patients, regardless of ICU admission, would be ideal for training in delirium detection and ensuring continuity of patient care during the postoperative period.…”
Section: Introductionmentioning
confidence: 93%
“…Inconsistent results have also been shown by recent reports of the diagnostic performance of the CAM‐ICU when used with postoperative older patients in non‐critical settings. Those studies showed a contrasting sensitivity from 25–80% and a high specificity (97–99%) . The data from previous research at the current study site showed that approximately 50% of patients aged ≥60 years were admitted postoperatively to the ICU .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Liang et al showed that when comparing those who developed post-operative delirium with those who did not, the former had a poorer preexisting cognitive function (59.5% vs. 37.0% of MMSE scores < 24, P < 0.007) [13]. Koskderelioglu et al showed that patients with cognitive impairment defined as a low MMSE score were more likely to have postoperative delirium (P = 0.001; odds ratio 0.75, 95% CI 0.65-0.86) [14]. A study by Heng et al showed that delirium was significantly increased in patients with an abnormal Mini-Cog© test and had an odds ratio of 3.22 (95% 1.59-6.77, P = 0.001) [15].…”
Section: Association Of Cognitive Impairment With In-hospital Outcomesmentioning
confidence: 99%